Construction of Writing Procedure for Getting Students to Produce Independent Academic Written Works - Gulieva Elnara Fakhretdinovna (Zien Journals, 2023)
Writing an academic essay in English refers to the scientific and creative type of independent work of students, the development of which is very difficult for bachelors of nonlinguistic specialties. The purpose of the article is to actualize the importance of pedagogical support of independent educational activities of students in the development of foreign language academic writing. The article presents the experience of using the modified technology of pedagogical support of students' independent work, characterizes the content of the stages of technology, describes the activities of the teacher and students in accordance with the peculiarities of mastering the academic essay.
Keywords: academic writing; academic essay in English; process-oriented approach; language experience